Techno-economic analysis in optimisation of hybrid air-conditioning system combining chilled water storage and solar water heater - Dzulaika Nubaillah, Noor (2019)
This thesis is a research report representing a study of hybrid air-conditioning combining vapour compression system, chilled water storage and solar water heater system in the tropical region. Yearly, solar radiation in the tropical climate promises potential exploitation of solar energy for cooling purposes. Solar air-conditioning system can be attractive to explore in the South East Asian region because of the abundance of solar radiation throughout the year. Solar energy is clean and provides no harm to the environment. Thus, development in solar air-conditioning in respective ways can give a good return to society. The main component in hybrid solar air-conditioning is the solar water heater system. Introduction of solar water heater system in the existing vapour compression system in the UMP library building can provide a new direction in the development of renewable energy projects especially in higher learning institutions such as Universiti Malaysia Pahang. The main issue of hybrid solar air-conditioning is the intermittant input because of the variation in daily weather conditions. As a hot and humid country, solar radiation can be useful in the early part of the year but turns less useful during the monsoon season towards the end of the year. Thus, the idea to sustain the hybrid solar air-conditioning can be supported by installing thermal energy storage (TES) to store energy for later use. The best and most economical TES is chilled water storage (CWS). Harvested solar radiation can be used to feed absorption chiller and this chiller mainly functions to chill the water. The chilled water will be distributed through the Air Handling Unit (AHU) for the following day’s usage. Any discrepancy of solar radiation should be covered by a supplementary unit of auxiliary heater. Modelling the hybrid component would be the most important part to get an optimum result in terms of economic and environmental saving. Weather data in Pekan was recorded yearly using the mini weather station installed by the Faculty of Mechanical Engineering. These data were used to determine the cooling load of UMP library building. Radiant Time Series (RTS) method was chosen according to ASHRAE 2009 by using the recorded local weather data and the UMP library building physical profiles. Result of the average cooling load was used to determine the optimum sizing of the chilled water storage tank. Manipulating the water tank size, the temperature difference and the operation hours can be good factors to get fairly good savings in economic and environmental terms. All operations were scheduled during night time in order to gain benefits on the off-peak electricity rate under Commercial Group. The environmental assessment was done using CO2 emission factor from International Energy Agency (IEA) Standard in 2015. The Payback Period analysis was used to determine the economic benefits. In conclusion, with optimum sizing and operation strategy the yearly billing of the building can be reduced up to RM405,470 and CO2 emissions can be reduced up to 296,638 kgCO2e/kW for the UMP library building. This research work can contribute to more incorporation of design and installation of solar air-conditioning hybrid systems in tropical countries in future to help reduce dependency of fossil fuels and reduce emissions of greenhouse gases to the atmosphere.